The Influence of Parent Parenting Patterns on Adolescent Association - Nurlela; Euis Habibbah Nurhasanah; Agung (Ilmu Inovasi Nusantara, 2023)
This study aims to determine parenting patterns and their impact on adolescent association in Dusun 2 Cibodas, Cipondok Village, Cibingbin sub-district, Kuningan Regency. which includes rules, controls, monitoring, guidance, reprimands, attention, examples or role models, and parental prohibitions. This type of research is descriptive using a qualitative approach. Respondents amounted to three people, namely parents who have teenage children. Data collection methods used in this study were interviews, observation, and documentation. Based on the results of the study, it was found that parents who apply authoritarian parenting to young women have a positive impact on the daily life of adolescents and are independent and achieve at school, can self-actualize well, and are far from environmental influences and bad associations. Parents who apply democratic parenting to adolescents who have an open mind tend to have a positive impact on their adolescents so that their adolescents can sort out and choose which associations are good and which are not good for them. Parents who apply permissive parenting tend to have a negative impact so that their teenagers drop out of school and prioritize mere pleasure without thinking about their future. It is suggested to parents to better understand their duties and functions as parents and understand what parenting styles are suitable in caring for their adolescents according to the circumstances and conditions of adolescents